Structural and optical properties of neodymium-doped zinc silicate-based glass ceramic - Mohd Ismail, Zamratul Maisarah (2018)
The need for fabricating low cost luminous material have gained considerable attention in optoelectronic field. Therefore, in this research, Zn2SiO4:Nd3+ based glass ceramic were prepared from recyclable waste soda lime silica (SLS) as silica source and ZnO using solid state method. The effect of Nd3+ ions (x = 0, 1, 2, 3, 4 and 5 wt.%) and the effect of sintering temperatures, ranging from 600 to 1000 °C on the thermal, structural, morphological and optical properties of the phosphors were also investigated using Differential Scanning Calorimetry (DSC), X-ray diffraction (XRD), Field emission scanning electron microscopy (FESEM), Fourier transform infrared (FTIR) spectroscopy, Ultraviolet-visible near infrared (UV-Vis-NIR) spectroscopy and Photoluminescence (PL) spectroscopy. Thermal analysis were carried out to determine the thermal stability and glass transition temperature of the sample. Structural investigation using XRD revealed the presence of α-zinc silicate phase at 800 °C onwards. The effect of sintering temperature showed phases changes and enhancement in crystallinity. With respect to Nd3+ doping, the diffraction peaks shifted due to lattice distortion. The morphologies from FESEM analysis showed the transformation in particles and grain boundaries formation. With increment in temperature and doping, the microstructure become densely packed grains. FTIR spectra showed that the progression of sintering temperature and doping revealed the existence of SiO4 and ZnO4 bonding which indicate the formation of Zn2SiO4 network. Furthermore, the optical properties of the Zn2SiO4:Nd3+ based glass ceramic were analysed for its UV absoprtion to determine the optical band gap. The optical band gap obtained were in the range 2.56 eV – 3.74 eV which is in agreement with WLEDs optical band gap. The increment and decrement of optical band gap (Egap) were speculated due to structural changes of host material and Burstein Moss effect. The photoluminescence spectra of Nd3+ ions exhibit blue to red emission at ~484 nm (blue), ~529–570 nm (green) and ~600-676 nm (orange-red) corresponding to transitions 2P1/2 → 4I11/2, 4G7/2 → 4I9/2, (4G7/2→4I11/2, 4G5/2→4I9/2), (4G5/2→4I11/2) and (4G7/2→4I13/2, 4G5/2→4I11/2) respectively. These spectra proved the incorporation of Nd3+ into Zn2SiO4 lattice. The emission intensity changes with respect to dopant percentage and sintering temperatures. The intensity of PL emission were affected by enhancement the crystallite of zinc silicate and Nd3+ ions into the crystals. Overall, from the obtained results this study concluded that Zn2SiO4:Nd3+ based glass ceramic have promising parameters for WLEDs application that exhibit blue to red region under infrared excitation.